Characterization of PNIPAAm-co-AAm hydrogels for modified release of bromelain. (August 2018) - Croisfelt, Fernanda Machado; Ataide, Janaína Artem; Tundisi, Louise Lacalendola; Cefali, Letícia Caramori; Rebelo, Marcia de Araújo; Sánchez, José Luis Dávila; da Costa, Tais Germano; Lima, Renata; Jozala, Angela Faustino; Chaud, Marco Vinicius; d'Ávila, Marcos Akira; Tambourgi, Elias Basile; et al.
Graphical abstract: Highlights: NIPAAm and AAm co-polymerized hydrogels presented 340% swelling ratio. Hydrogel reached 30% of protein loading. Release studies pointed to an initial burst release, followed by controlled release. Hydrogels micropores and bromelain loading were confirmed by SEM. Rheology tests confirmed typical behavior of crosslinked hydrogels. Abstract: Thermosensitive materials, such as PNIPAAm, are considered for the development of hydrogels for controlled release, especially for topical use. Bromelain is a set of proteases found in plants (Bromeliceae family) and it is known for having several medical uses, including healing of topical wounds. The combination of PNIPAAm hydrogels and bromelain could result in a potential formulation for topical injuries. In this work, different NIPAAm hydrogels were submitted to swelling tests for 24 h. The selected formulation presented a swelling ratio of 340%, and was used for bromelain loading, reaching up to 30% of protein loading. After loading, hydrogel disks were dried and immersed in phosphate buffer (pH 7.0) for release study. Release studies pointed to an initial burst release, followed by a modified (slower) release, reaching its optimum enzymatic activity release rates at around 60 min in both temperatures (25 °C and 37 °C). Scanning electron microscopy and Fourier transform infrared spectroscopy confirmed bromelain loading through hydrogen bonds, without interfering in intermolecular polymeric chains. Bromelain presence decreased mucoadhesion at 25 °C and increased at 37 °C; it also increases polymers crosslink, without interfering in elastic properties (drilling and resilience). Hydrogels (blank and loaded with bromelain) showed a typical behavior of crosslinked hydrogels at rheology tests, and bromelain increased storage modulus. Both hydrogels showed a significant cell death after 24 h in NIH/3T3 cell line.